The effects of adolescent methamphetamine exposure - Buck, Jordan M.; Siegel, Jessica A. (Frontiers in Neuroscience, 2015)
Methamphetamine use among adolescents is a significant social and public health concern. Despite increased awareness of methamphetamine use among younger people, relatively little research has examined the effects of adolescent methamphetamine use compared to adult use. Thus much remains to be learned about how methamphetamine alters adolescent brain function and behavior. In this article we review recent trends in adolescent methamphetamine use and data examining the effects of adolescent methamphetamine use on the dopaminergic system and behavior in humans and animal models. Future research is warranted to expand our understanding of the effects of adolescent methamphetamine exposure and how those effects differ from those seen in adults.